Assessment of weight gain during pregnancy in general prenatal care services in Brazil - Luciana Bertoldi Nucci; Bruce Bartholow Duncan; Sotero Serrate Mengue; Leandro Branchtein; Maria Inês Schmidt; Eni Teresinha Fleck
Obesity is an emerging major health risk for women around the world. In this regard, little attention has been given to pregnancy, a moment of risk not only for major weight gain in these women, but also for macrosomia in their offspring. The objective of this study is to evaluate weight gain during pregnancy. Data pertains to a cohort of pregnant women attending general prenatal care clinics in six state capitals in Brazil, from 1991 to 1995. We studied women aged 20 years and over with singleton pregnancies and no diagnosis of diabetes outside pregnancy, enrolled at approximately 20 - 28 weeks of gestation. According to the Institute of Medicine criteria, 38% (95%CI: 36-40%) of the women studied gained less and 29% (95%CI: 28-31%) had more than the recommended total weight gain. These proportions vary according to pre-pregnancy nutritional status. Given the increasing epidemic of obesity, the high prevalence of overweight and obesity in Brazilian women prior to pregnancy, and the lack of achievement of recommended weight gain during pregnancy, more effective means of managing weight gain during pregnancy are necessary.